Coaching to Augment Mentoring to Achieve Faculty Diversity: A Randomized Controlled Trial - Williams, Simon N. (Acad Med, 2016)
PURPOSE: The Academy for Future Science Faculty (the Academy) is a novel coaching intervention for biomedical PhD students designed to address limitations in previous efforts to promote faculty diversity. Unlike traditional research mentoring, the Academy includes both group and individual coaching, coaches have no research or evaluation roles with the students, and it is based on social science theories. The authors present a qualitative case study of one of the coaching groups and provide statistical analyses indicating whether one year in the Academy effects students’ perceptions of the achievability and desirability of an academic career. METHOD: The authors have tested (July 2012-July 2013), with Northwestern University ethical approval, the Academy via a longitudinal randomized controlled trial. Participants were 121 latter-stage biomedical PhD students. The authors collected data via questionnaires, interviews, and meeting recordings. RESULTS: The case study shows how group career coaching can effectively supplement traditional one-to-one research mentoring; provide new role models for underrepresented minority students; and provide theory-based lenses through which to engage in open conversations about race, gender, and science careers. Repeated-measures analysis of variances showed perceived achievability increased in the Academy group from baseline to 1-year follow-up (means, 5.75 vs. 6.39), but decreased in the control group (6.58 vs. 5.81). Perceived desirability decreased significantly less (P < 0.05) in the Academy group (7.00 vs. 6.36), than in the control group (7.83 vs. 5.97). CONCLUSIONS: Early results suggest that an academic career-coaching model can effectively supplement traditional research mentoring and promote persistence towards academic careers.